INFLUENCE OF BRAND IMAGE AND CUSTOMER SATISFACTION TO BRAND LOYALTY THROUGH BRAND LOVE AS A MEDIATION VARIABLE IN STARBUCKS MULTATULI MEDAN - Muhammad Ismuroji; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (CV. Radja Publika, 2023)
Along with rising population and income levels, it has become a major factor in the rising demand for non-consumption-based necessities, which many have adopted as a way of life. The expansion of the Coffee Shop industry has made coffee an integral part of people's lifestyles. Starbucks' continued existence depends on customer loyalty. Starbucks Multatuli's efforts to maintain brand loyalty are still relatively low. Customers continue to prefer other coffee shops over Starbucks. However, the customer's affection for Starbucks will cause the customer to form an emotional bond with Starbucks. Consequently, the customer's emotional attraction to Starbucks and feelings of pleasure will increase customer satisfaction. Thus, a positive brand image will provide customers with a positive experience, which will foster a sense of love for Starbucks and increase brand loyalty. This study's objective is to examine how brand image and customer satisfaction influence brand loyalty via brand love. Four variables comprise the survey: brand image, customer satisfaction, brand loyalty, and brand love. Accidental sampling is used for sampling. The population of this study consisted of 120 Starbucks Multatuli customers who participated in the survey. Using the SmartPLS 3.0 application, PLS-SEM was utilized for data analysis. The results indicated that brand image and customer satisfaction had a significant effect on brand love, a significant effect on brand loyalty, and a significant effect on brand loyalty via brand love.